The Impact of Role-Playing Game Experience on the Sustainable Development of Ancient Architectural Cultural Heritage Tourism: A Mediation Modeling Study Based on S-O-R Theory - Siqin Wang; Junjie Yu; Weijia Yang; Wenjun Yan; Ken Nah (Buildings)
Role-playing games (RPGs) set in ancient architecture have emerged as a digital tool for enhancing engagement with ancient architectural cultural heritage. This study examines how RPG elements (immersion, narrative, cognitive engagement) influence sustainable tourism outcomes at ancient architectural heritage sites and develops a stimulus–organism–response (SOR)-based framework model to explore their affective and behavioral effects. The results demonstrate that immersion, narrative, and cognitive engagement in RPGs significantly enhance tourists’ affective engagement. Affective engagement, in turn, enhances tourists’ willingness to travel to and support for heritage conservation sites. Mediation analyses indicated that affective engagement partially mediated the effects of immersion and narrative on the willingness to travel and fully mediated the effects of cognitive engagement. Affective engagement positively predicted support for heritage preservation, whereas willingness to travel alone did not exhibit this relationship. Emotional engagement is therefore a critical mechanism by which digital role-playing game experiences drive sustainable tourism behaviors, resulting in outcomes that go beyond individual behaviors to include broader sustainability impacts. By fostering immersive, narrative-rich, and engaging cognitive experiences, RPGs set in ancient architecture can stimulate willingness to visit heritage sites and encourage conservation awareness, providing valuable insights into sustainable tourism and the management of ancient architectural heritage.